Identifying A Sustainable Tourism Development Model for The Amungme Tribe Community at Mimika Regency Papua Province - Teddy Tandaju; Steven Y. Kawatak; Mesak Kadepa (Journal of International Conference Proceedings (JICP), 2020)
Amungme Tribe, residing in Mimika Regency, has important roles in developing the Papua Province’s tourism sector. Up to now, this tribe has experienced various obstacles in developing its community and region. Authors conducted a qualitative-based method research to find strategies to elevate this tribe to have competitive advantages to increase its prosperity. In this research, surveys and in-depth interviews with relevant stakeholders were conducted in Timika City to generate effective strategies. Authors have designed a comprehensive approach, namely Amungme-Based Sustainable Tourism (ABST), which focuses on the development of 4Rs: Revitalization, Reconstruction, Remuneration, and Reconciliation. Through effective and efficient applications of 4Rs, it is expected that there will be great changes for Amungme Tribe and the community of Mimika Regency.